"Águas profundas": representações sociais do risco para profissionais que trabalham em plataformas de petróleo. - Mariano, Igor de Almeida Rizzo (2019)
Offshore oil exploration has required professional companies willing to expose themselves to the risks inherent in offshore activity. The issue of risk in hazardous activities has always been addressed in companies with the objectivity of engineering. The purpose of this study is to offer a discussion about “risk in offshore work” from a psychosocial perspective, using the Social Representation Theory (SRT) as a theoretical and conceptual basis. The survey included 12 professionals working on boarding on oil rigs of the same company, being a semisubmersible platform and 4 FPSO platforms, encompassing both sexes, different job functions and time of varied professional experience. The methodological procedure for approaching the participants was through the snowball technique (“snowball”), where people from the researcher's relationship network were asked to know workers with the appropriate research profile to indicate possible interviewees, repeating this technique with indications of the interviewees themselves. In the data collection stage, a semi-structured interview was used, addressing sociodemographic questions, as well as questions that allowed access to elements of social representations of risk in offshore work. The textual data of the interviews were submitted to a computational treatment using the IRAMUTEQ software, and analyzed using the Lexical Analysis, Specificity Analysis and Descending Hierarchical Classification (CHD), the latter resulting in 4 speech classes. The final results showed that in the social representation of risk for offshore professionals there are elements that can be associated with the reified universe (technical guidelines on the risks to which they are exposed and on procedural rules), as well as elements belonging to the consensual and practical universe - the “Fears” (such as helicopter trip to the platform), accidents. The data allow us to conclude that there is a singular 11 appropriation of the reified universe by the professional public, where there is a smaller distance from this universe to the consensual one, besides highlighting the metaphor of the lion and the cage as objectification of risk for these workers.